EU health information progress: the harvest of policy supporting projects and networks - Mariken J. Tijhuis; Linda A. Abboud; Peter W. Achterberg (BMC, 2022)
Abstract Background The European Commission supports the initiation of health information related projects and networks serving comparative population health monitoring and health system performance assessment. Many of these projects and networks have produced relevant data, standards, methods, indicators and knowledge that may be lost as these networks become inactive. The aim of this project retrieval and review was to identify health information projects and networks and their produced output; and subsequently facilitate systematic access to this information for policy makers, researchers and interested others via a web-based repository. Methods The scope of this article covers 1. population health oriented topics and 2. health system/health services oriented topics. Out of scope are specific infectious diseases; individual rare diseases; and the occurrence and effects of specific medical treatments, interventions and diagnostics; cohort studies; or studies focusing on research methods. We searched bibliographic databases and EU project databases for policy supporting projects and networks and selected those fulfilling our inclusion criteria after more in-depth inspection. We searched for their outputs. In addition, we reviewed country participation in these projects and networks. Results We identified 36 projects and networks, 16 of which are population health oriented, 6 are health systems and services oriented and 14 cover both. Their total volume of output is not easily retrievable, as many project websites have been discontinued. Some networks and/or their outputs have found continuance within European agencies and/or national institutions. Others are struggling or have gone lost, despite their policy relevance. Participation in the projects was not evenly distributed across Europe. Project information was made available through the Health Information Portal. Conclusions EU funded projects and networks have contributed greatly to the evidence-base for policy by providing comparative health information. However, more action is needed to evaluate and conserve their outputs and facilitate continued contribution to the field after project funding stops. The realization of a sustainable infrastructure for these projects and networks is urgent. The Health Information Portal can play an important role in conserving and reusing health information. Information inequalities may exist across Europe but need further investigating.